Carbohydrates : the essential molecules of life - Stick, Robert V. (Elsevier, 2009)
This book provides the "nuts and bolts" background for a successful study of carbohydrates - the essential molecules that not only give you energy, but are an integral part of many biological processes. A question often asked is 'Why do carbohydrate chemistry?' The answer is simple: It is fundamental to a study of biology. Carbohydrates are the building blocks of life and enable biological processes to take place. Therefore the book will provide a taste for the subject of glycobiology